Ambient temperature and hospital admissions for acute cholecystitis: a nationwide inpatient database study in Japan. Issue 3 (March 2022) - Miyakawa, Teppei; Michihata, Nobuaki; Morita, Kojiro; Matsui, Hiroki; Honda, Michitaka; Yasunaga, Hideo
Abstract: Background: The incidence of acute cholecystitis has a seasonal peak in summer. However, the reason for such seasonality remains unclear. This retrospective cohort study was performed to examine the association between ambient temperature and acute cholecystitis. Methods: We identified admissions for acute cholecystitis from January 2011 to December 2017 from a nationwide inpatient database in Japan. We performed a Poisson regression analysis to investigate the association between ambient temperature and admission for acute cholecystitis with adjustment for relative humidity, national holidays, day of the week, and year. We accounted for clustering of the outcome within prefectures using a generalized estimating equation. Results: We analyzed 601 665 admissions for acute cholecystitis. With an ambient temperature of 5.0 °C–9.9 °C as a reference, Poisson regression showed that the number of admissions increased significantly with increasing temperature (highest above 30 °C; relative risk, 1.35; 95% confidence interval, 1.34–1.37). An ambient temperature of <5.0 °C was also associated with higher admission for acute cholecystitis than an ambient temperature of 5.0 °C–9.9 °C (relative risk, 1.23; 95% confidence interval, 1.21–1.25). Conclusion: The present nationwide Japanese inpatient database study showed that high temperature (≥10.0 °C) and low temperature (<5.0 °C) were associated with increased admission for acute cholecystitis.